2007
DOI: 10.1017/s0143385707000053
|View full text |Cite
|
Sign up to set email alerts
|

Invariant densities for generalizedβ-maps

Abstract: We find an explicit formula for the invariant density of a generalizedβ-map. This allows us to also find an explicit formula for the invariant density of Chebyshev map and discuss the monotonicity of the asymptotic average for such maps. Our results are based on a generalization of works of Parry (Acta Math. Acad. Sci. Hungar. 11(1960), 401–416;15(1964), 95–105).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 15 publications
(22 reference statements)
2
48
0
Order By: Relevance
“…Similar to Lemma 10 in [7], we get that h * β,E is non-negative. Since ψ β,E (1/β) = β · 1 0 h * β,E dm > 0, we get the conclusion.…”
Section: Where F (β E) Denotes the Normalizing Factor For The Invarisupporting
confidence: 60%
See 1 more Smart Citation
“…Similar to Lemma 10 in [7], we get that h * β,E is non-negative. Since ψ β,E (1/β) = β · 1 0 h * β,E dm > 0, we get the conclusion.…”
Section: Where F (β E) Denotes the Normalizing Factor For The Invarisupporting
confidence: 60%
“…In [7] Góra showed that every map τ β,E has a unique absolutely continuous invariant probability measure μ β,E and its density function h β,E can be expressed by using the coefficients of the τ β,E -expansion of 1. Precisely, the density function h β,E is expressed as n+1 .…”
mentioning
confidence: 99%
“…The curve α = 0 is a trivial example of such a curve for the fixed point x = 0. In section 4, we study the generalized β-transformations introduced by Góra [7]. A generalized β-transformation is similar to a β-transformation, but each lap is replaced by an increasing or decreasing lap of constant slope β according to a sequence of signs.…”
Section: B Faller and C-e Pfistermentioning
confidence: 99%
“…Introduced by Góra in [7], they have only one critical orbit like β-transformations, but they admit increasing and decreasing laps. A family {T β } β>1 of generalized β-transformations is defined by k ≥ 2 and a sequence s = (s n ) 0≤n<k with s i ∈ {−1, 1}.…”
Section: Normality In Generalized β-Transformationsmentioning
confidence: 99%
See 1 more Smart Citation